2020
DOI: 10.6118/jmm.19021
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Pharmacological Treatments for Vaginal Atrophy in Postmenopausal Women in Iran

Abstract: Vaginal atrophy is one of the most common menopausal complications and is often overlooked. There are various pharmacological and non-pharmacological treatment approaches to reduce vaginal atrophy; however, no comprehensive study on a convenient, affordable, inexpensive, and noninvasive treatment with fewer complications has been conducted so far. Thus, the current study aimed to provide a systematic review of pharmacological treatment for vaginal atrophy in postmenopausal women in Iran. In this systematic rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…This could be attributed to factors such as job loss, reduced social interactions, limited educational opportunities, recreational constraints, and diminished freedom as they spend more time at home. Research suggests that certain measures implemented to combat the pandemic may disproportionately affect vulnerable groups, such as the unemployed [10]. Within this study, the "Other" group, consisting of mothers with children, pregnant women, and students, emerges as particularly susceptible to mental health challenges induced by the pandemic.…”
Section: Discussionmentioning
confidence: 92%
“…This could be attributed to factors such as job loss, reduced social interactions, limited educational opportunities, recreational constraints, and diminished freedom as they spend more time at home. Research suggests that certain measures implemented to combat the pandemic may disproportionately affect vulnerable groups, such as the unemployed [10]. Within this study, the "Other" group, consisting of mothers with children, pregnant women, and students, emerges as particularly susceptible to mental health challenges induced by the pandemic.…”
Section: Discussionmentioning
confidence: 92%
“…In addition to the above explanation, other factors that can affect the level of stress in pregnant women include the fact that pregnant women are more vulnerable to viral infections (Fakari & Simbar, 2020), making them susceptible to COVID-19 infection due to their lowered immunity caused by hormonal changes during pregnancy (Yolanda, Bakhtiar, Putri, & Firgantri, 2021). This can lead to psychological effects on pregnant women, including stress, anxiety, and depression (Yuanti et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The results of the present study and of other have studies indicate that high levels of toward RID were prevalent during pandemics across various countries. Studies have reported that high levels of worry toward infection are associated with psychological distress physical health issues, and stigma [11,25,26]. Therefore, health professionals must provide appropriate psychological interventions for reducing worry [27].…”
Section: Discussionmentioning
confidence: 99%